One night with the Duke / Belmore Square - Malpas, Jodi Ellen (New York : Forever, 2023)
"It's 1814 and nineteen year old Eliza Melrose is about to be launched into London's high society-much to her dismay. The last thing she wants is a husband. Eliza's "misplaced" thirst for adventure, knowledge and creativity is a bone of contention for her father, who battles endlessly to keep her curiosity and ambitions in check, for women are not meant to ask questions or give opinions in matters of business. But then she meets the youngest son of the late Duke of Chester, a disgraced nobleman who is shrouded in mystery and proving quite impossible to resist.."--
Originally published in 2022 by Orion Books in Great Britain.
Keywords: Romance fiction; Novels